PENERAPAN TEKNOLOGI PESTISIDA NABATI DAN HAYATI DALAM RANGKA MEMPERKUAT BUDIDAYA PADI BERBASIS ORGANIK DI DESA PELIATAN UBUD KABUPATEN GIANYAR BALI - Ida Bagus Swaputra; Ni Gst. Ag. Gde Eka Martiningsih; I Nyoman Gde Maha Putra; I Nyoman Patra; I Ketut Widnyana (Forum Layanan IPTEKS Bagi Masyarakat (FLipMAS) Wilayah Bali, 2019)
The Teges Subak group and the Subak Putungan group face problems in controlling pests and diseases in rice and secondary crops. In rice plants farmers are very disadvantaged by attacks of pests and diseases that cause rice plants to become puso (empty grains and red stems). The attack of pests and diseases causes rice production to decrease by more than 50%, which is very detrimental to farmers in Subak Teges and Subak Putungan. The main objectives of the program to implement appropriate technology to the community of these farmer groups are (1) To help farmers in integrated pest and disease control technology, (2) Providing productive rice planting techniques, (3) Providing training in the manufacture of locally based plant-based pesticides, (4)Providing techniques for making biological pesticides based on Trichoderma sp, Metharizium sp, and Glyocladium sp, (5) Providing techniques for the application of vegetable and biological pesticides to rice plants, (6) Training farmers in the technique of monitoring pests and diseases in the field. The method used is counseling, training and mentoring. The expected outcome of this community-based application of appropriate technology activities is; 80% of farmers understand and are skilled in making vegetable and biological pesticides, 90% of farmers understand and are skilled in implementing integrated pest and disease control technology and 90% of farmers understand and are skilled in monitoring pests and diseases in the field, farmers are able to produce 50 liters of vegetable pesticides themselves, farmers are able to produce50 kg of their own biological pesticides, attacks of pests and diseases have decreased by 75%.